INTEGRITATE SI LIBERTATE DE CONȘTIINȚĂ. O INCURSIUNE ÎN SCRIERILE CREȘTINE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrity and freedom of Conscience. A Brief Foray into Christian WritingsThe theme about freedom of conscience was always important, therefore many theologians wrote about this subject along centuries. No matter the background( historical, political, religious or cultural), the human being always wanted to decide on his own his religious beliefs. This was not always possible. Political and religious leaders, dictatorship governments or national churches often forced people’s choices about their beliefs. Some accepted what they were being forced to believe, some just faked their emotions, while others understood that they have to remain strong in their faith. Theologians such as Iustin the Martyr, Tertulian, Augustine, Martin Luther, Balthasar Hubmeier, Roger Williams, James Madison, Warren Wiersbe have had an important role in promoting the freedom of conscience. Looking at their writings, we can see that moral integrity plays an important role in promoting freedom of conscience, a necessary element in a world with deviant principles.